Kepuasan Siswa Sekolah Dasar Terhadap Pembelajaran Daring di Tengah Pandemi Covid-19 - In’amatul Azimah; Fajar Setiawan; Lilik Binti Mirnawati (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study was to identify information about the satisfaction of teaching and learning online at home due to the Covid-19 pandemic. The research method used is the survey method, with the instrument used is a questionnaire through a Google form that is distributed to elementary school students. In this study, respondents were elementary school students in the city of Surabaya. Word has circulated that online learning is less effective, because there is no maximum preparation in terms of regulation, field implementation and also students, as well as supporting infrastructure for online learning, therefore researchers have a desire to test the satisfaction level of online learning. Because there can be no learning content lost in the middle of this pandemic. The results of this study there are several obstacles experienced by students, teachers and parents in online learning activities, namely lack of technology mastery, additional internet quota fees, additional work for parents in assisting children's learning, communication and socialization between students, teachers and parents become less.